CLINICAL, HAEMATO - BIOCHEMICAL, RADIOLOGICAL AND HISTOPATHOLOGICAL STUDIES OF HORN AFFECTIONS IN BUFFALOES - K. Rama Rao; Makkena Sreenu; K.B.P. Raghavender; P .V. S. Kishore (Indian Journal of Veterinary and Animal Sciences Research, 2024)
A study was conducted in buffaloes suffering with horn affections .The physiological and haematological parameters were within the normal limits in all the horn affections, but the plasma cortisol and C-reactive protein were more than the normal levels in all the horn affections for initial periods. A radiological sign like increased radio-opacity was noticed in the septic horn cases. Microscopic examination of biopsy samples of horn and skin following amputation revealed normal histology except in horn cancer where squamous cell nests and mitotic figures in the squamous cells were observed.